Patterns of student socio-emotional development and teacher-student-relationship-quality for high-school students with and without special educational needs: a multigroup latent transition analysis approach for low and high selective schools - Giuliana Pastore; Wassilis Kassis; André Kunz; Reto Luder (Frontiers in Education, 2025)
IntroductionA positive socio-emotional development of students within the school context lies basically in their perception of wellbeing, social inclusion and academic self-concept. The teacher-student-relationship-quality (TSRQ) plays here a key role, especially for students with special educational needs (SEN). There is empirical evidence that student development and TSRQ are linked in various ways to different types of SEN, and that the school model (low versus highly selective) can shape them differently. For this reason, the question was addressed whether different patterns of student development and TSRQ can be longitudinally identified. In addition, we tested whether having SEN or being in a high vs. low selective schools make a difference for the composition of each profile.MethodsTo this end, latent class (LCA) and latent transition analyses (LTA) were conducted with longitudinal data from a three-waves (2019, 2020, and 2021) questionnaire study with N = 807 junior high school students in Switzerland.ResultsFour similar patterns could be identified in both low and high selective schools: “happy” students, feeling generally well (emotionally, socially and cognitively) and well-supported by teachers; “unhappy” students, not feeling well and not supported, “teacher-oriented” students, not feeling well but well-supported by teachers, and finally “unstable” students, drastically changing their perceptions of wellbeing, inclusion and self-concept over time but consistently feeling less reliance on teachers. Particularly striking is the result showing that high selective schools “produce” more “unhappy” (58.2%) then “happy” students (32.8%) whereas in low selective schools 67.2% of the students are “happy.” Further, school-selectivity can significantly explain the probability to fall into the profile “unhappy” in high selective schools and “teacher-oriented” in low selective schools. Having SEN can significantly predict the profiles “unhappy” and “teacher-oriented” in low selective schools but is not predictive for the profile “unstable.” In high selective schools it seems to be irrelevant whether students have SEN or not for the likelihood of being in any profile.